ANALYSIS OF FACTORS RELATED TO HEMOGLOBIN (Hb) LEVELS IN PATIENTS UNDERGOING HEMODIALYSIS (HD) AT BHAYANGKARA HOSPITAL SURABAYA - Singgih; Ariska Putri (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Kidney failure (CKD) is a disease that results in reduced kidney function. One of the complications of CKD is anemia. Anemia caused by decreased erythropoietin, shortened red blood cell life span, gastrointestinal bleeding due to toxic irritation and blood loss during hemodialysis. The research design used is correlational research. The type of research used is a cross-sectional study. The population of this study was 60 patients undergoing hemodialysis at Bhayangkara Hospital Surabaya who experienced anemia in the hemodialysis room at Bhayangkara Hospital Surabaya. Sampling used a probability sampling technique, namely proportionate stratified random sampling. The instrument in this research is a checklist sheet. The independent variables in this study include the length of time the patient underwent hemodialysis, the patient's nutritional status and HD adequacy. The data analysis used was the Rank - spearmen test. The research results from 60 respondents, the majority (38.3%) underwent HD for 6 - 8 years. The nutritional status of most patients (67%) was normal. The HD adequacy rate achieved in the hemodialysis room was 40 respondents (67%). The spearmen's rank test calculated significantly the patient's nutritional status, and the achievement of HD adequacy with Hb levels with a p-value of 0.000 (a < 0.05), which means there is a relationship between nutritional status and the achievement of HD adequacy and the Hb levels of patients undergoing hemodialysis at Bhayangkara Hospital, Surabaya. So it is stated that H0 is rejected and Ha is accepted. Then, for the length of HD factor, calculated using the Spearman's rank test, the p-value was 0.18 (a > 0.05), which means there is no relationship with the Hb level of patients undergoing HD at Bhayangkara Hospital, Surabaya, so it is declared that H0 is accepted and Ha is rejected. The conclusion of this research is that nutritional status and HD adequacy factors have a significant relationship with Hb levels in the Hemodialysis Room at Bhayangkara Hospital, Surabaya. It is hoped that this research can be applied by researchers with related parties (research sites).